2021
DOI: 10.1016/j.ejrad.2021.109645
|View full text |Cite
|
Sign up to set email alerts
|

Novel flat-panel cone-beam CT compared to multi-detector CT for assessment of acute ischemic stroke: A prospective study

Abstract: Cone beam CT (CBCT) imaging assessment of acute ischemic stroke (AIS) patients with large-vessel occlusion (LVO) in the angiosuite may improve stroke workflow and decrease time to recanalization. In order for this workflow to gain widespread acceptance, current CBCT imaging needs further development to improve image quality. Our study aimed to compare the image quality of a new CBCT protocol performed directly in the angiosuite with imaging from multidetector CT as a gold standard. Methods: AIS patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Traditional utilizations of non-contrast CBCT, either before the thrombectomy as a substitute of the traditional CT scanner or during/after the thrombectomy to rule out a hemorrhage, are very well detailed elsewhere. 22 The roles of HR-CBCT angiography during stroke thrombectomy are infrequent. They include the evaluation of collaterals 23 or the visualization of vessels distally to a point of occlusion, through an acquisition obtained during intra-arterial injection from the ascending aorta.…”
Section: Strokementioning
confidence: 99%
“…Traditional utilizations of non-contrast CBCT, either before the thrombectomy as a substitute of the traditional CT scanner or during/after the thrombectomy to rule out a hemorrhage, are very well detailed elsewhere. 22 The roles of HR-CBCT angiography during stroke thrombectomy are infrequent. They include the evaluation of collaterals 23 or the visualization of vessels distally to a point of occlusion, through an acquisition obtained during intra-arterial injection from the ascending aorta.…”
Section: Strokementioning
confidence: 99%
“…[1][2][3][4] However, due to a number of factors including X-ray scatter, beam hardening artifacts, and detector limitations, conventional flat detector systems currently provide limited discrimination between low contrast tissues,such as white and gray matter in the brain. 1,5 Furthermore, conventional CBCT is limited to imaging with full energy spectrum integration and cannot be used to estimate effective atomic number or electron density (ED) within different tissues. Atomic number and ED can be used to differentiate between tissues and are of interest both in diagnostic radiology and for radiotherapy planning.…”
Section: Introductionmentioning
confidence: 99%
“…We have noticed an improvement in overall quality of cone-beam CT over the past few years. First, shorter acquisition times accompanied by higher doses and advanced postprocessing were shown to improve image noise, artifacts, and gray/white matter differentiation for circular scans 5. Although there have been many improvements since the first maxillofacial examination in 1994, CBCT image quality could be further improved by increasing the radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CBCT imaging is reliable for hemorrhage characterization,1 2 which can be of great value during long or complex procedures where bleeding risks are high, such as arteriovenous malformation or fistula embolizations. Detection of ischemic lesions using CBCT is also possible,3–5 which has supported a sparked interest towards using this technology in patients presenting with acute ischemic stroke (AIS). Ideally CBCT could be used for treatment triage of patients with AIS and hopefully used to bypass the need for conventional CT to bring patients directly to the angiography suite for mechanical thrombectomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation